Agricultural mechanization and agricultural transformation - Diao, Xinshen; Silver, Jed; Takeshima, Hiroyuki (International Food Policy Research Institute, 2016)
A renewed focus on agriculture’s potential contribution to economic transformation in Africa has resulted in increased attention paid to agricultural mechanization. African agriculture still relies predominantly on human muscle power despite anecdotal evidence on urbanization and rising rural wages, in contrast to other developing regions that have experienced rapid increases in agricultural mechanization during the past few decades. Past state-led mechanization pushes in Africa often failed due to insufficient understanding of the nature of demand for mechanization technologies among farmers and insufficient knowledge of private-sector functions. This background paper reviews the factors likely to influence farmer demand for mechanization in Africa and details different existing and potential mechanization supply models. Although an empirical analysis of mechanization demand and the effectiveness of supply chains is beyond the scope of this paper, in part due to data limitations, this paper suggests that demand for mechanization may be emerging in some parts of Africa. It also suggests that private-sector-driven supply models are better positioned to meet this demand than direct government involvement and certain types of subsidized programs. The paper then identifies possible areas for government support to complement private-sector leadership in developing mechanization supply chains. Nevertheless, significant further research is required to better understand the changing nature of mechanization demand in Africa and the extent and effectiveness of different supply models in meeting it.